2007
DOI: 10.1038/sj.eye.6702931
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic vitreolysis with recombinant microplasminogen and tissue plasminogen activator

Abstract: Purpose To generate microplasmin (lPlm) using recombinant microplasminogen (lPlg) and recombinant tissue plasminogen activator (rt-PA) before intravitreous injection and to investigate the efficacy of lPlm in inducing posterior vitreous detachment (PVD). Methods Forty-eight female or male New Zealand white rabbits were randomized into three groups. Recombinant human lPlg was incubated with rt-PA with a 200:1 molar ratio at 371C for 40 min. The right eyes of groups 1, 2, and 3, were injected with 0.5, 1.0, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…The results suggest that microplasmin (5 mg kg )1 ) induced less intracranial hemorrhage than did t-PA, and perhaps decreased cerebral injury better than t-PA, but one study [64] suggested that a higher micro-plasmin dose (10 mg kg )1 ) offered no advantage and perhaps contributed to higher mortality. Micro-plasmin has also been assessed for vitreolytic effects in cat [65], rabbit [66] and pig [67] models, with microgram amounts being injected locally to induce detachment of vitreous cortex from retina.…”
Section: Micro-plasminmentioning
confidence: 99%
“…The results suggest that microplasmin (5 mg kg )1 ) induced less intracranial hemorrhage than did t-PA, and perhaps decreased cerebral injury better than t-PA, but one study [64] suggested that a higher micro-plasmin dose (10 mg kg )1 ) offered no advantage and perhaps contributed to higher mortality. Micro-plasmin has also been assessed for vitreolytic effects in cat [65], rabbit [66] and pig [67] models, with microgram amounts being injected locally to induce detachment of vitreous cortex from retina.…”
Section: Micro-plasminmentioning
confidence: 99%
“…The initial pre-clinical studies revealed achievement of complete PVD (eg, bare ILM) at doses ranging from 62.5–125.0 μg (equivalent to 1–2 U of plasmin) in enucleated human eyes with or without adjunctive intraocular gas 148. In-vivo studies similarly exhibited complete PVD following 7–21 day intravitreal microplasmin exposure with doses differing based on species; cat eyes achieved PVD at doses of 14.5–25.0 μg,148 while two separate studies in rabbits reported consistent PVD at doses of 125–250 μg 149,150. No histologic toxicity148150 or functional toxicity149 was noted excepting persistent a- and b-wave depression on ERG testing in the 250 μg group only.…”
Section: Vitreolytic Agentsmentioning
confidence: 92%
“…In all treated eyes, there was a temporary reduction in the a-and b-wave amplitudes on electroretinography, which recovered by 14 days after injection in all except for the 250 lg group. Most recently, Chen et al [41] used immunofluorescent histochemistry to find that intravitreal ocriplasmin degraded fibronectin and laminin, not only at the vitreoretinal interface but also at the level of the photoreceptor layer in the outer retina of rats-a potentially untoward effect. MIVI-I (Intravitreal Microplasmin During Surgical Vitrectomy) was the first study to examine the safety and preliminary efficacy of a single ocriplasmin injection in humans, over a range of doses and exposure times.…”
Section: Ocriplasminmentioning
confidence: 98%